DESAIN SKENARIO PEMUNCULAN TINGKAT KESULITAN SOAL PADA GAME MATEMATIKA MENGGUNAKAN APLIKASI RULE-BASED SYSTEM (RBS) - Minarto Minarto (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
In playing games a student (player) sometimes forgets the time, even sacrifices learning time to play the game. That thinking is what underlies this research, that learning while playing is expected to be a solution to increase students' interest in learning. To adjust the scenario to the player's ability, a scenario with varying difficulty levels is prepared. The scenario referred to here is the emergence of problems, so there are also problems with three levels of difficulty, namely easy questions, medium problems, and difficult questions. To determine the center of the cluster, if the difficulty level of the problem is between 0.71 - 1.00 then the problem can be said to be an easy matter, and the range of 0.71 - 1.00 can also be called the easy cluster range, while the cluster center is 0.86, if the difficulty level of the problem is between 0.31 - 0.70 then including the medium problem, and the range of 0.31 - 0.70 can also be called the medium cluster range, while the center of the cluster is 0.50, and if the difficulty level of the problem is between 0.00 - 0.30 then the problem can be said to be a difficult problem, and the range of 0.00 - 0.30 can also be called the difficult cluster range, while the cluster center is 0.15. The Rule-Based System will be used to form rules to direct players to scenarios that match the player's own abilities.